STRUKTUR KEPEMILIKAN, KEBIJAKAN DIVIDEN DAN NILAI PERUSAHAAN MANUFAKTUR YANG GO PUBLIC - I Ketut Yadnyana; Ni Wayan Alit Erlina Wati (Jurnal Keuangan dan Perbankan, 2011)
The aim of this study was to obtain the empirical evidence about the effect of managerial ownership structureand dividend policy on company value. This study consisted of 66 manufacturing companies which hadshared dividends in year period of 2005 until 2008 with 161 observations. The certainty sample method usedwas purposive sampling. Statistics methods used for testing the hypothesis were simple linear regression andmultiple linear regression method. Based on the statistical test showed that positive impact of managerialownership was on dividend policy and firm value. It showed that the greater level of managerial ownershipwas followed the increasing of dividends value paid to the shareholders and it also caused the value ofcompanies getting better. The variables of dividend policy caused positive impact for the companys value. Theresult showed that larger the dividend distributed to the shareholders, the better the value of the company was.